1976
DOI: 10.1111/j.1570-7458.1976.tb02576.x
|View full text |Cite
|
Sign up to set email alerts
|

BIOASSAY OF PINE OIL COMPONENTS AS ATTRACTANTS FOR SIREX NOCTILIO (HYMENOPTERA: SIRICIDAE) USING ELECTROANTENNOGRAM TECHNIQUES

Abstract: A study was made of the response to components of pine oils and related compounds of antennae excised from female Sirex noctilio using electroantennogram (EAG) techniques. A response ratio of each compound was obtained after determining the response expected from the same amount of linalool, which was used as a reference material. Correlations were found between activity and chemical structure. Within each chemical class, compounds having a pinane skeleton and unsaturation showed the highest response. Activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 7 publications
1
33
2
2
Order By: Relevance
“…11 , 12 ). However, evidence continues to suggest that additional volatile compounds may be involved in signaling since girdled and/or herbicide-treated trap trees (Madden 1971 ;Morgan and Stewart 1972 ;Neumann et al 1982 ;Simpson 1976 ;Simpson and McQuilkin 1976 ) nearly always outperform artifi cial traps baited with the recommended mixed-pinene lure.…”
Section: Factors Contributing To Tree Susceptibilitymentioning
confidence: 97%
“…11 , 12 ). However, evidence continues to suggest that additional volatile compounds may be involved in signaling since girdled and/or herbicide-treated trap trees (Madden 1971 ;Morgan and Stewart 1972 ;Neumann et al 1982 ;Simpson 1976 ;Simpson and McQuilkin 1976 ) nearly always outperform artifi cial traps baited with the recommended mixed-pinene lure.…”
Section: Factors Contributing To Tree Susceptibilitymentioning
confidence: 97%
“…It is a long-recognized fact that S. noctilio is attracted to the stems of stressed pine trees (95,96) (Figure 2). A large number of volatile compounds (>60) are associated with such pine stems, with the bulk of these made up of monoterpene hydrocarbons (>95%) such as α-and β-pinene (29,95,96).…”
Section: Chemical Ecologymentioning
confidence: 99%
“…A large number of volatile compounds (>60) are associated with such pine stems, with the bulk of these made up of monoterpene hydrocarbons (>95%) such as α-and β-pinene (29,95,96). Pheromone: chemicals produced by individual organisms that affect the behavior of other members of its species (Figure 2).…”
Section: Chemical Ecologymentioning
confidence: 99%
“…Several studies have shown that stressed pine trees are primarily attacked by the European woodwasp, apparently attracted by volatiles, which are released from the stem (Simpson 1976). The volatile composition of pine trees and the antennal responses they elicit in the European woodwasp have been studied in some detail by American researchers (Crook et al 2012).…”
Section: The European Woodwaspmentioning
confidence: 99%